An Alternate Graft for Staged Flexor Tendon Reconstruction. (March 2015) - Low, N.; Fahy, E. T.; Frisken, J.; Mann, N.
We describe the novel use of semitendinosus as a tendon graft for 2-stage flexor digitorum profundus (FDP) reconstruction. To our knowledge, this is the first reported use of a hamstring tendon graft in this setting. The FDP of two digits were reconstructed in a 30 year-old male who presented 18 years after the original injury. The semitendinosus was chosen as a graft as the traditional grafts were deemed inappropriate. The result of the operation is convincing, and we suggest the semitendinosus tendon to be considered an option for FDP reconstruction.